PROFIL KESLAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA FPB DAN KPK BERDASARKAN NEWMAN ERROR ANALYSIS SERTA PEMBERIAN SCAFFOLDING DI SMP NEGERI 2 DOMPU - Ewan Gunawan; Lale Ajeng Khalifatun Wardani; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
The ability to solve mathematical word problems is an important indicator in measuring students' problem-solving skills. However, many students still make errors when solving word problems, particularly in the topics of the Greatest Common Divisor (GCD) and the Least Common Multiple (LCM). This study aims to describe the types of students' errors based on the Newman Error Analysis (NEA) framework and to describe the forms of scaffolding provided to address these errors. The study employed a descriptive qualitative approach involving three seventh-grade students from SMP Negeri 2 Dompu, who were selected purposively based on the results of a pretest. Data were collected through written tests, in-depth interviews, documentation, and the provision of scaffolding. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that students made five types of errors according to Newman's framework: reading errors, comprehension errors, transformation errors, process skills errors, and encoding (final answer) errors. The most dominant errors occurred at the transformation and process skills stages. The implementation of scaffolding in the forms of explaining, reviewing, and restructuring was proven to help students correct their errors in solving GCD and LCM word problems. The posttest results showed an improvement in students' abilities after receiving scaffolding, indicating that this approach is effective for use in mathematics instruction. making learning more meaningful, improving students' understanding of geometric concepts, and fostering students' appreciation for regional cultural heritage.